Variation in neutrophil levels and artemisinin-based combination therapy efficacy in West-Africa - Moussa Djimde; Kassoum Kayentao; Japhet Kabalu Tshiongo; Bakary Fofana; Charles Arama; Sodiomon B Sirima; Jean Bosco Ouedraogo; Abdoul Habib Beavogui; Issaka Sagara; Alassane Dicko; Petra F Mens; Henk DFH Schallig; et al. (Journal of Infection in Developing Countries)
Introduction: Polymorphonuclear neutrophils (PMN) are involved in pathogen clearance by phagocytosis. However, the role of PMNs in the efficacy of artemisinin-based combination therapy (ACT) is poorly understood.